A Production Systems Study of Acquisitions International Trading - Arreola, Edylil; Dela Cruz, Alfred Jojo G.; Dioco, Everett C.; Pua, Kerry Y. (College of Engineering, 1995)
Acquisitions International Trading, AIT, is an export-oriented job shop firm that manufactures wrought iron/wood furnitures and accessories. It is divided into six major departments, employing a total workforce of 45 people, excluding a few casual and contractual workers. The company has a materials-oriented location. It does not depend solely on one suppler of their raw material requirements. The main production layout adopts a layout by process arrangement, except for the first few production processes that make distinction between the wood and wrought iron products. The company is in the process of constructing their new building, situated just at the back of their present site. The study team will analyze the production system using the total systems approach with emphasis on production, specifically, production planning and control. However, in-depth analysis of the wood production was not employed due to the low production of wood products during the study period. Emphasis was given on the wrought-iron production and the finishing department. The end objective of the study was satisfying customer demands as quickly as possible, and minimizing production cost by good production planning. The two main problems discussed in this paper are poor production planning and poor layout. After the objectives were set and problems were identified, the study team proceeded to the actual gathering of data. A time and motion study was necessary in order to come up with standards to analyze and give proposals on how to increase the company's productivity and efficiency. From these data, capacity planning was conducted to determine the optimum number of workers required for each process. The result of the study show that the company is not working at its full capacity. At the finishing department, the 6 workers currently employed averages only 200 units per month, whereas it has the potential to produce 600 units per month. The company is only 33.33% efficient, exhibiting signs of poor production planning and control. From the time study, the team was also able to identify the bottleneck operation--that of the finishing department. Because of these findings, the study recommended the following changes: construction of a balanced production line, stronger quality policies, implementation of a production planning board, and decentralization of the company's original structure. As a consequence of the construction of a production line, smoother flow of work will ensue and WIP will be minimized. The implementation of stronger quality policies, coupled with the decentralization of its implementation, will allow for defects to be detected at their earliest stages and save a lot in terms of raw materials and time. Worker empowerment is recommended to involve the workers and make them more quality conscious. The production planning board, PPB, will facilitate and improve scheduling. The PPB will provide the discipline that the workers need in order complete their tasks on time. Closer monitoring of the progress of jobs with respect to the planned schedules will reduce worker initiativeness. Supervisors will be trained in proper scheduling and monitoring. the PBB will also serve as the link between the management and the supervisors. and the supervisors and the workers. Decentralization of the organizational structure will remove a lot of responsibility, especially in terms of quality inspection , from the shoulders of the management. This will allow them more time to search for more demands to meet their capacity. Decentralization will also encourage involvement among workers. The study team recommended a layout for the new site of the company. The group used a nearness string rating in order to minimize travel distances between consecutive processes. The layout reduces congestion that impedes movement of materials by designating a permanent place for everything. However, flexibility was also emphasized. Other recommendations by the group include good housekeeping, improvement of working conditions and better methodology. The effects of these recommendations are more subtle and harder to quantify, but this does not undermine the importance they give.